Letter: assessing iron deficiency in patients with IBD—a step in the right direction, but uncertainty remains. Issue 2 (26th June 2020) - Garg, Mayur; Chand, Sheital; Weenink, Petrus; Yunqiu Wu, Karen; Cheng, Richard K. Y.
Abstract : LINKED CONTENT This article is linked to Daude et al paper. To view this article, visit https://doi.org/10.1111/apt.15739 .